Ocorrência de Gerreidae (Osteichthyes, Perciformes) no canal de Camboatá, sistema lagunar de Itaipu-Piratininga, RJ: abundância relativa e cronologia alimentar - Silva, Maria Helena Carvalho da (1994)
This paper contributes to the knowledge of Gerreidae species participation in tropical lagoon environments, with special reference to the Camboatá channel that interconnects the lagoon system Itaipu-Piratininga. The main objective being the analysis of the temporal distribution, the feeding chronology and teh condition factor of the species. From October to August of 1991, samples were taken with cast-net and gill-net in eight series along 24 hours cycles, with two series per season of the year. The Gerreidae family is represented by its great variety of species, constituted by Gerres aprion, G. lefroyi, G. melanopterus, G. gula, G. cinereus, Diapterus richii, D. rhombeus and D. lineatus. The constancy, frequency and relative abundance indicate that G. aprion is a resident estuarine species, that centralizes the grouping of G. lefroyi, · D. richii and D. rhombeus constitued by cyclical visits. G. melanopterus and G. gula are occasional visitors while D. lineatus in an accessory species and G. cinereus is considered an accidental.The specimens of Gerreidae were represented by juveniles in their first year of life, during the whole sampling period with predominance with very young individuals in autumn and in winter. The six most representative species were diurnal fedeers with feeding activities most intense during the morning period to dusk hours. The homogeneous distribution of these species is possibly associated with the good condition of their well being in the different seasons of the year or 24 hour cycle, in periods of biotic factor variation. The Camboatá channel and associated subsystems are utilized by juveniles of Gerreidae as recruitment area, shelter and feeding sites, characterizing the importance of this lagoon system for the species studied.